Bakhtin and his Others (inter)subjectivity, chronotope, dialogism - Steinby, Liisa; Klapuri, Tintti (Anthem Press, 2013)
Bakhtin and his Others offers fresh theoretical insights into Bakhtins ideas on (inter)subjectivity and temporality, research into his theoretical backgrounds, and case studies where these insights are employed in literary analysis